Dr. Akinwumi A. Adesina speeches - Conference Center - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Dr. Akinwumi A. Adesina giving speeches at IITA Conference Center at 50th anniversary of the institute.